Spectrum of MDP Bone Scan in Paediatric Patients - Experience at NINMAS - Mutsuddy, Pupree; Begum, Shamim MF; Sultana, Nasreen; Parveen, Rahima; Ali, Nabeel Fahmi; Chaudhury, Amardeep; Banu, Layla Saroware (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: To assess the clinical indications and spectrum of MDP bone scan findings in paediatric patients referred to the National Institute of Nuclear Medicine and Allied Sciences (NINMAS). Materials and Methods: Paediatric patients, age ranged from 2-18 years referred to NINMAS from January 2014 to November 2015 for bone scintigraphy were included in this study. All patients had 99mTc MDP bone scan for various clinical indications. The spectrum of clinical indications and bone scan findings were recorded and analyzed. Results: Total 2323 bone scans with 99mTc MDP were done in NINMAS in the above mentioned period. Among them 91 (3.917%) cases were in paediatric age group. Of which 82 (90.11%) patients with known malignancy were referred for radionuclide skeletal survey. The most common clinical indications were osteosarcoma 30 (32.96%) cases and Ewing’s sarcoma 25 (27.47%) cases followed by five neuroblastoma (5.49%), four (4.39%) rhabdomyosarcoma, three (3.29%) Langerhans cell histocytosis and rest others. Bone scan was positive in 58 (63.7%) cases and normal in 33 (36.3%) cases. Out of 58 cases 38 had features of primary bony lesion, 10 cases had multiple metastases, four cases had primary bone tumour of Ewing’s sarcoma as well as metastases. Conclusion: Bone scan is a popular imaging modality for skeletal survey of paediatric patients in malignancy, both primary and metastatic bone diseases. Bone scanning in paediatric patients contributes a major role in detecting the cause and localizing the pathology of bone. High quality imaging, interpreted by physicians familiar with paediatric diseases, correlation with clinical records and other imaging are mandatory to maximize the benefit. Bangladesh J. Nuclear Med. 19(1): 28-31, January 2016